Laser-Aided Ceramic Bracket Debonding: A Comprehensive Review - Ghazanfari, Rezvaneh; Nokhbatolfoghahaei, Hanieh; Alikhasi, Marzieh (Journal of Lasers in Medical Sciences, 2016)
Different techniques have been introduced for the removal of ceramic brackets. Since the early 1990s, lasers have been used experimentally for debonding ceramic brackets. The goal of this study is to give a comprehensive literature review on laser-aided ceramic bracket debonding. PubMed and Google Scholar databases were used to identify dental articles with the following combination of key words: Ceramic brackets, Debonding, and Laser. Sixteen English articles from 2004 to 2015 were selected. The selected studies were categorized according to the variables investigated including the intrapulpal temperature, shear bond strength, debonding time, enamel damage and bracket failure. Most articles reported decreased shear bond strength and debonding time following laser irradiation without any critical and irritating increase in pulpal temperature. There were no reports of bracket failure or enamel damage. Laser irradiation is an efficient way to reduce shear bond strength of ceramic bracket and debonding time. This technique is a safe way for removing ceramic bracket with minimal impact on intrapulpal temperature and enamel surface and it reduces ceramic bracket failure.